Marginal Unit vs. Marginal Unit — some additional thoughts on the differences between Menger, Jevons, and Walras - Machaj, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Scholars usually trace the basics of the neoclassical theory back to the marginal revolution, in which three great thinkers amended the fundamentals of modern consumer and production theory. Scholars also recognize, however, important differences between those three thinkers’ works — in the nature of the neoclassical framework and its application to the real world, especially in the field of political economy. In this note, we argue that the main difference in these works, not identified in previous publications on the subject of “dehomogenization”, is their understanding of the marginal unit. We demonstrate the relevance of this important difference in the socialist-calculation debate
Keywords: Jevons, William Stanley (1835-1882); Menger, Carl (1840-1921); Walras, Léon (1834-1910); marginalizm; neoklasycyzm; szkoła austriacka